Methane Gas Production In Buffalo Rumen Fluid Containing Citronella Residue (Cymbopogon nardus L.) by In Vitro Method - Sari, Arina Findo; Mangunwardoyo, Wibowo; Setiawan, Fery Hadi; Sugoro, Irawan (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
Methane is one of the greenhouse gases produced by ruminants. One way to reduce methane is by feeding development strategies. Concentrates or forage are two possible forms of animal feed. Forage can be replaced with citronella (Cymbopogon nardus L.) residue, which has not been fully consumed as feed. The purpose of the study was to decide the production of methane gas that has residual citronella to concentrate in buffalo rumen fluid in vitro, for 48 hours. The treatments in this research were 0.4 g citronella residue (A); 0.4 g citronella residue + 0.01 g concentrate (B); 0.4 g citronella residue + 0.02 g concentrate (C); 0.01 g concentrate (D); and 0.02 g concentrate (E). For the 48-hour measurements, the highest methane gas production was treatment 98.2% (D); followed by 92.06% (E); 17.71% (C); 15.33% (A); and 13.54% (B). It can be concluded that methane gas can be reduced by residue citronella. This shows that citronella residue can lower methane gas. The study's findings are anticipated to be among the references for using agricultural product residues, particularly citronella as animal feed to reduce the methane produced by the livestock industry